Chemoenzymatic Halocyclization of γ, δ‐Unsaturated Carboxylic Acids and Alcohols. Issue 1 (30th December 2019) - Younes, Sabry H. H.; Tieves, Florian; Lan, Dongming; Wang, Yonghua; Süss, Philipp; Brundiek, Henrike; Wever, Ron; Hollmann, Frank
Abstract: Invited for this month's cover is the group of Prof. Dr. Frank Hollmann at Delft University of Technology in the Netherlands. The Front Cover shows the vanadium‐dependent haloperoxidase from the marine organism Curcuvaria inaequalis, which efficiently activates halides as hypohalites that can then initiate spontaneous halo‐lactonization and halo‐etherification reactions. The Communication itself is available at 10.1002/cssc.201902240 . Abstract : "leaving the niche of high‐value‐added fine chemicals…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201902240 . View the Front Cover here: 10.1002/cssc.201903373 .